Understanding Syrian refugees’ experience in terms of settlement and participation in Canadian labour market: A mixed method approach - Seo, Bosu; Lowney, Krystal (Advances in Social Sciences Research Journal, 2021)
This paper explores Syrian refugees’ experience in terms of settlement and participation in Canadian labour market. It discusses the findings of research on labour market integration in Canada of racialized immigrants and refugees, as well as the state of economic insecurity among newcomers, to identify systemic patterns of discrimination and policy implications. A mixed method approach with in-depth interview and questionnaire surveys were used for an analysis. Long-term benefit, second-generation success, and reliance on government support were commonly observed. Language barrier, lack of host country’s experience, and lack of transportation were cited as common barriers to employment. This research confirms that there is no uniform process for refugees entering into a host country. Canadian government needs to create a structured program to be implemented in each province and deliver the same process for every refugee entering.